Adolescents’ Knowledge of Early Marriage using Audiovisual Media and Leaflet Intervention at Pelita Insani Vocational School - Lestari, Diah Ayu; Nesa Ayu Murthisari Putri (Jurnal Midwifery, 2025)
Background: Early marriage remains a global problem requiring serious attention. In Indonesia, data shows that 8.16% of women marry at ages 10-15, with South Sumatra still above the national average. Low knowledge among adolescents about the impacts of early marriage requires effective educational interventions. Objective: This study aims to determine the effectiveness of audiovisual media and leaflet interventions in improving adolescent knowledge about early marriage at SMK Pelita Insani Prabumulih. Methods: This study used a quantitative method with a Quasi Experimental Pre-Post Test With Control Group design. The study population was 100 respondents using total sampling technique. The intervention group was divided into two: audiovisual group (n=50) and leaflet group (n=50). Data were analyzed using Independent T-Test and Mann-Whitney Test. Results: Respondent characteristics showed the majority aged 17-18 years with predominant female gender. In the audiovisual group, the median knowledge score increased from 60 to 62, while in the leaflet group from 65 to 67. Statistical analysis showed significant differences (p<0.05) in both groups. Audiovisual media provided 6.4 times higher risk for knowledge improvement (95% CI: 2.376-4.610, p=0.000), while leaflet media provided 4.4 times higher risk (95% CI: 1.335-2.577, p=0.000). Conclusion: Both intervention media (audiovisual and leaflet) are effective in improving adolescent knowledge about early marriage with statistically significant differences. Audiovisual media shows higher effectiveness compared to leaflet media in improving adolescent knowledge about early marriage